2021
DOI: 10.7759/cureus.13819
|View full text |Cite
|
Sign up to set email alerts
|

Stay-At-Home Orders Are Associated With Emergence of Novel SARS-CoV-2 Variants

Abstract: Background While public health strategies to contain the current coronavirus disease 2019 (COVID-19) pandemic are primarily focused on social distancing and isolation, emerging evidence suggest that in some regions social isolation failed to lead to further decrease in the number of COVID-19 deaths in the long run. This apparent paradox was particularly observed in the northern region of Brazil, in the state of Amazonas. We hypothesized that the emergence of new severe acute respiratory syndrome cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…We identified 10 studies which contributed data relevant to modifying infection-control procedures which are summarized in Table 4. Of these 10 studies, 8 were modeling, 50, 5962 lab-based 63, 64 or grey literature 65 and thus not critically appraised. Of the two that were appraised, one was high quality, 27 and the other was medium quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 10 studies which contributed data relevant to modifying infection-control procedures which are summarized in Table 4. Of these 10 studies, 8 were modeling, 50, 5962 lab-based 63, 64 or grey literature 65 and thus not critically appraised. Of the two that were appraised, one was high quality, 27 and the other was medium quality.…”
Section: Resultsmentioning
confidence: 99%
“…Somewhat supporting that household transmission may be a key feature to monitor in VOC outbreaks, a study conducted by Zimerman et al in Brazil, reported contrasting findings in terms of outbreak management. 62 In their study comparing prevalence of the P.1 variant with social isolation data, authors found that prevalence of P.1 actually increased when individuals remained within 450m of their home. This study therefore highlights the need to tailor public health measures to specific populations and that vigilance regarding household transmission is warranted.…”
Section: Changing Approach To Outbreak Managementmentioning
confidence: 99%
“…The Variant PCR incorrectly interpreted several other lineages to be either B.1.1.7 or B.1.351/P1. Interestingly, all these wrongly interpreted lineages had biologically important mutations and were in fact “variants of interest” [21] . Sixteen samples defined as potentially B.1.1.7 by Variant PCR were B.1.525, a variant of interest, lacking the N501Y spike mutation but possessing the biologically important E484K mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Early COVID-19 treatment may be especially effective in developing countries where mass vaccination is in progress, but only on a small scale. In such countries, non-pharmacological measures to curb the pandemic are difficult to deploy because of social inequalities and illiteracy, and these methods might be associated with the appearance of dangerous SARS-CoV-2 variants [ 44 ], themselves a potential worldwide threat. Furthermore, in such countries, epidemiological surveys suggest that early COVID-19 treatment may be associated with decreased mortality [ 45 ].…”
Section: Discussionmentioning
confidence: 99%